Modular synthesis of 1-α- and 1-β-(indol-2-yl)-2'-deoxyribose C-nucleosides - Nečas, David; Hidasová, Denisa; Hocek, Michal; Kotora, Martin (Organic & biomolecular chemistry, 2011)
A simple two-step method for the selective preparation of anomerically pure 1α- and 1β-(indol-2-yl)deoxyribose derivatives was developed. The synthesis was based on the Sonogashira reaction of 1α- and 1β-ethynyldeoxyribose and 2-haloanilines followed by a Pd-complex catalyzed cyclization to the corresponding indolyldeoxyribosides.
Keywords: deoxyribosa; Cyclization; nukleosidy; cyklizace; indoly; Indoles; Catalysis; Nucleosides; Deoxyribose; katalýza